2014
DOI: 10.1186/1746-1596-9-20
|View full text |Cite
|
Sign up to set email alerts
|

Significance of ERβ expression in different molecular subtypes of breast cancer

Abstract: PurposeThis study is to investigate the estrogen receptor β (ERβ) expression in molecular subtypes of breast cancer and clinic significance of ERβ expression.MethodThe ERβ expression was detected in 730 cases of breast cancer tissue specimens by immunohistochemistry. Twenty-one patients were censored during 2–10 years follow-up. The difference in ERβ expression was analyzed by Pearson Chi-square Test. Its correlation with estrogen receptor α (ERα), progesterone receptor (PR) and human epidermal growth factor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
(19 reference statements)
0
10
1
Order By: Relevance
“…ERβ positivity (96.8%) in our series is much higher than that in previous studies, which reported rates of 25% in triple-negative cancers54 and 37.6% in basal-like breast cancers 55. To the best of our knowledge, there have been no reports of ERβ on purely metastatic TNBC.…”
Section: Discussioncontrasting
confidence: 74%
“…ERβ positivity (96.8%) in our series is much higher than that in previous studies, which reported rates of 25% in triple-negative cancers54 and 37.6% in basal-like breast cancers 55. To the best of our knowledge, there have been no reports of ERβ on purely metastatic TNBC.…”
Section: Discussioncontrasting
confidence: 74%
“…The heterogeneity of breast cancer includes differences in ethnicity, menopausal status, ER/PR status, HER-2/neu expression, and other molecular signatures [30,31]. Finding the sources of breast cancer heterogeneity would contribute to subtype specific therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the frequency of ERβ expression in breast tumors has been reported to range from 17-100% [ 15 , 18 , 21 35 ] and from 13-83% in ERα negative breast cancer [ 17 , 24 , 29 , 30 , 33 , 36 ]. With regard to the biological functions of ERβ, a number of studies have shown that the presence of this receptor correlates with improved rates of recurrence, disease-free survival and overall survival [ 22 , 24 27 , 37 41 ] while others indicate little to no correlation [ 28 , 30 , 38 ] or even worse prognosis [ 33 , 42 – 44 ]. Lastly, several studies have reported that the presence of ERβ in breast tumors increases the effectiveness of tamoxifen therapy [ 36 , 45 48 ] or aromatase inhibitor therapy [ 47 , 49 ].…”
Section: Introductionmentioning
confidence: 99%